2020
DOI: 10.1080/21663831.2020.1739156
|View full text |Cite
|
Sign up to set email alerts
|

Origin of high strength in the CoCrFeNiPd high-entropy alloy

Abstract: Recent experiments show that the CoCrFeNiPd high-entropy alloy (HEA) is significantly stronger than CoCrFeNi and with nanoscale composition fluctuations beyond those expected for random alloys. These fluctuations were suggested to be responsible for strengthening. Here, a recent parameterfree theory for initial yield strength in fcc random alloys is shown to predict the strength of CoCr-FeNiPd in good agreement with experiments. The strengthening is due mainly to the large misfit volume of Pd in CoCrFeNi, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 33 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…Solute strengthening in NiCoCr: theory versus experiment. With the experimental misfit volumes and two recent literature values for the room temperature single-crystal elastic constants 30,31 , we can predict the initial yield strength of NiCoCr within the framework of an existing solute strengthening theory for random alloys 32,33 , which has previously shown quantitative success for a number of HEAs 25,[32][33][34][35][36] . We can then compare the random alloy strength prediction against experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Solute strengthening in NiCoCr: theory versus experiment. With the experimental misfit volumes and two recent literature values for the room temperature single-crystal elastic constants 30,31 , we can predict the initial yield strength of NiCoCr within the framework of an existing solute strengthening theory for random alloys 32,33 , which has previously shown quantitative success for a number of HEAs 25,[32][33][34][35][36] . We can then compare the random alloy strength prediction against experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The idea was that SRO tends to create resistance to deformation/slip, leading to larger dislocation glide resistance in the more ordered CoCrFeNiPd than in CoCrFeNiMn HEAs. Theoretical work by Yin et al 22 suggested that the strengthening was due mainly to the large atomic/misfit volume of Pd in CoCrFeNi. Ma et al 23 identified a number of unusual features associated with dislocations/slips in HEAs that were related to lattice distortion and/or local chemical order.…”
Section: Introductionmentioning
confidence: 99%
“…This approach relies on the evaluation of the interaction energy between dislocations and solutes of different sizes. The model can be parameterized from DFT calculations but in its simplest elastic version, it relates the yield stress at 0 K denoted τ y0 to the misfit parameter δ as [17,18,19]:…”
mentioning
confidence: 99%